2011
DOI: 10.1103/physrevlett.107.190403
|View full text |Cite
|
Sign up to set email alerts
|

Condensed Fraction of an Atomic Bose Gas Induced by Critical Correlations

Abstract: We study the condensed fraction of a harmonically trapped atomic Bose gas at the critical point predicted by mean-field theory. The nonzero condensed fraction f(0) is induced by critical correlations which increase the transition temperature T(c) above T(c) (MF). Unlike the T(c) shift in a trapped gas, f(0) is sensitive only to the critical behavior in the quasiuniform part of the cloud near the trap center. To leading order in the interaction parameter a/λ(0), where a is the s-wave scattering length and λ(0) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 38 publications
(52 reference statements)
4
25
0
Order By: Relevance
“…Deviations from the mean-field prediction and effects due to critical correlations have been measured in Refs. [13,14]. A major breakthrough has been achieved recently with the realization of Bose-Einstein condensation in quasiuniform trapping potentials [15].…”
mentioning
confidence: 99%
“…Deviations from the mean-field prediction and effects due to critical correlations have been measured in Refs. [13,14]. A major breakthrough has been achieved recently with the realization of Bose-Einstein condensation in quasiuniform trapping potentials [15].…”
mentioning
confidence: 99%
“…Several studies on the homogeneous Bose gases found that repulsive interactions decrease the critical temperature [23][24][25], but most studies pointed to an increase of the critical temperature [26][27][28][29][30][31][32][33][34]. The critical temperature of a trapped Bose gas has also been studied experimentally [35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…(34), the first term provides the condensate fraction in the thermodynamic limit. The second term, which is vanishes for T > 1, provides a consistent way for treating the interaction effect [36][37][38][39].…”
Section: µ0(t =0)mentioning
confidence: 99%